Contextual-Based Knowledge Creation for Agroindustrial Innovation - Elisa Anggraeni; Machfud Machfud; Mohamad Syamsul Maarif; Hartrisari Harjomidjojo (Gadjah Mada International Journal of Business, 2017)
This paper discusses the knowledge creation process in one department, in a higher educational context, and the possible actions to take to improve the efficiency and effectiveness of the knowledge creation system in it. We conducted a case study at one department of a university that strives to improve its innovations, in terms of their quantity and quality.We used a soft system methodology to investigate the knowledge creation system in the chosen department. From the study, we conclude that the department can be considered as a learning organization, within which its staff continually create, acquire and transfer knowledge. This department has a learning environment which is conducive, concrete learning processes, and leadership that reinforces learning. In the context of producing agroindustry innovations, the knowledge creation system in this department is considered to be less effective since it frequently happens more at individual or small group levels. To improve its effectiveness, the management may facilitate the institutionalization of knowledge creation processes at every phase of the interactions between tacit and explicit knowledge.